Birds of grey: Hunters of the sky - Alan Richards (Courage Books, 1998)
The book describes some of the characteristics of birds of grey; hooked beaks, sharp, powerful claws, penetrating eyes, magnificent feathers, and hunter instinct. It presents about 35 kinds of feathered hunters, such as the majestic eagle, the mysterious owl, and the breathtaking falcon